EFFECTS OF LYSINE SUPPLEMENTATION ON PERFORMANCE CHARACTERISTICS AND MINERAL RETENTION OF BROILER CHICKENS FED RAW BENNE SEED BASED DIETS - Akanji, A. M.; Fasina, O. E. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
The objective of the study was to determine the effects of raw benne seed (RBS, Sesamum indicum) with or without lysine supplementation on the performance characteristics and mineral retention of broiler chickens. The feeding trial lasted for 56 days. One hundred and forty unsexed day old  broiler chicks (Marshall strain) were used for the study. RBS was incorporated into the diets at 15% and 30% levels and  supplemented with  0%, 0.25% and 0.5% of lysine, respectively. Average  weekly feed intake in birds fed the control diet and 15% RBS based diet supplemented with 0.25 % and 0.5% lysine were not significantly different, but significantly (P